Sleep habits and problems across gestational progress in Japanese women. Issue 4 (6th February 2023) - Kawakami, Sho‐Ichi; Ikegami, Azusa; Komada, Yoko
Abstract: Background: Pregnancy‐related anatomic, physiologic, and hormonal factors can occur at different stages of pregnancy and affect sleep disturbances. Sleep problems and habits among Japanese women across gestational stages have not been described. This study aimed to elucidate sleep problems, including a high risk of sleep‐disordered breathing and sleep habits, among Japanese women across gestational progress, including postpartum. Methods: A questionnaire survey using the Pittsburgh Sleep Quality Index (PSQI) and Berlin Questionnaire was conducted for 683 pregnant women (223 in the second trimester, 453 in the third trimester) and 386 postpartum (within 1 week after delivery). Results: The total PSQI score was 5.3 [2.6] in the second trimester, 6.1 [2.8] in the third trimester, and 6.8 [3.1] in the first week postpartum. The percentage of those at high risk for sleep‐disordered breathing, as determined by the Berlin Questionnaire, was 11.8% in the second trimester, 21.3% in the third trimester, and 19.2% in the first week postpartum, with the highest percentage of those at high risk in the third trimester of pregnancy. Conclusion: The PSQI total score exceeded the cut‐off value in the third trimester and the first week postpartum, suggesting sleep deterioration. Therefore, it is necessary to understand and support sleep in pregnant women to ensure safe delivery, postpartum recovery, and health.